A critical evaluation on maximum power point tracking methods for partial shading in PV systems - Ahmed, Jubaer (Elsevier, 2015)
As photovoltaic (PV) system suffers considerable energy loss due to partial shading (PS), various approaches have been proposed to mitigate this problem. Among these, improving the maximum power point tracker (MPPT) algorithm seems to be the most feasible and economical solution. To date, there appears to be an absence of a single review paper that critically evaluates the performance of various types of MPPT algorithms during PS. To fill this gap, fifty prominent works on PS are analyzed from the theoretical and operational point of view. In particular, the paper will closely address the accurate detection for PS occurrence and the efficiency of global peak tracking. For certain selected cases, in-depth analysis is carried out to allow for an improved understanding on the operational intricacies of the algorithm. It is envisaged that this review paper would be a valuable one-stop reference to enable PV professionals to make more informed decisions when designing or choosing new MPPT algorithms for their inverters.